Bioinspired ultrasound-responsive fluorescent metal–ligand cross-linked polymer assemblies. Issue 17 (11th April 2017) - Wang, Zhenhua; Wang, Zhanhua; Xia, Hesheng
Abstract : We proposed a general strategy to construct bioinspired ultrasound-responsive fluorescent metal–ligand cross-linked polymer assemblies. Abstract : Inspired by the jellyfish breathing, we developed a novel strategy to construct an ultrasound-responsive fluorescent polymer assemblies. Upon exposed to ultrasound, the assemblies underwent a significant drop in fluorescence intensity (>80%), solution transmittance and particle size. Re-addition of zinc salt can restore the fluorescence and size of the assemblies.